A fragment to the genre of the piano piece - Bogunović Hočevar, Katarina (Muzikološki zbornik, 2006)
In spite of its small quantity, in its own way the piano opus of Janko Ravnik marked the history of Slovene piano music. Particularly with his early piano works, Ravnik opened up new dimensions in Slovene pianistic creativity. Addressing question as to whether we can speak of his piano compositions as the beginning of the piano piece in Slovenia, the present article seeks an answer on two levels: the compositional-technical and reception.
Keywords: klavirska miniatura; Ravnik, Janko, 1891-1982; slovenska glasba